2011
DOI: 10.3928/01913913-20100920-03
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Early Postoperative Outcomes of Pediatric Cataract Surgery With IOL Implantation From Lahan, Nepal

Abstract: A high-volume cataract surgical center in Lahan, Nepal, is able to provide cost-effective and high-quality pediatric surgery. Most of the patients in this series were noted to have complete cataracts and were boys. Visual improvement was achieved, but excellent visual outcomes were rarely documented due to late referral and inadequate follow-up. Educating families and primary caregivers with regard to the importance of earlier referral and postoperative optical correction and tracking will improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 6 publications
4
19
2
Order By: Relevance
“…Presence of nystagmus has poor visual outcome (P=0.022) similar to other studies (Tomkins et al, 2011;Wilson et al, 2010) but Young et al (2012) and Bradford et al (1994) has suggested that its presence is not a poor prognostic factor. Presence of strabismus has no significant correlation with visual outcome (P=0.64).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Presence of nystagmus has poor visual outcome (P=0.022) similar to other studies (Tomkins et al, 2011;Wilson et al, 2010) but Young et al (2012) and Bradford et al (1994) has suggested that its presence is not a poor prognostic factor. Presence of strabismus has no significant correlation with visual outcome (P=0.64).…”
Section: Discussionsupporting
confidence: 83%
“…The visual outcome was better than the study done in tertiary eye center Lahan (Wilson et al, 2010) and poor than study done by Bowman in Tanzanian children (Bowman et al, 2007) and Cassidy in London (Cassidy et al, 2001). There was a significant correlation between preoperative vision and improvement of vision postoperatively (P=0.001) which is similar to study done by Bowman et al where preoperative blindness was the strongest predictor of poor postoperative visual outcome (Bowman et al, 2007).…”
Section: Discussioncontrasting
confidence: 54%
“…The high proportion of traumatic cataract in this series is worth noting, being higher than studies from Southern Ethiopia (36.3%),15 Madagascar (25.6%)11 and Nepal (23.9%) 3. In contrast, in high-income settings, trauma accounts for only 10%–29% of cases 27.…”
Section: Discussioncontrasting
confidence: 56%
“…Numerous studies on traumatic paediatric cataract have been published from Asian countries such as India, (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Pakistan, (15,16) Nepal (17)(18)(19) and Korea. (20) However, a PubMed database search of published literature on traumatic paediatric cataracts from developing countries in the Southeast Asian region revealed that no such data is available.…”
Section: Introductionmentioning
confidence: 99%